Focal spinal intramedullary cysticercosis - Agrawal, R.; Singh Chauhan, S.; Misra, et al., V. (Acta Biomedica Atenei Parmensis, 2008)
Neurocysticercosis is the most common parasitic infestation of the CNS. Most authors have reported the incidence of spinal neurocysticercosis as only 1.5-3% of all cases, even in endemic areas. Spinal neurocysticercosis represents a distinct clinical entity that usually appears due to mass effect on the spinal cord. Most cases occur in the spinal subarachnoid space and cysticercosis in intramedullary location is extremely rare. The authors present a case of focal intramedullary spinal cysticercosis. The authors highlight the strategy for successful treatment of focal lesions in the intramedullary location.